Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/en12112157
|View full text |Cite
|
Sign up to set email alerts
|

DC Grid for Domestic Electrification

Abstract: Various statistics indicate that many of the parts of India, especially rural and island areas have either partial or no access to electricity. The main reason for this scenario is the immense expanse of which the power producing stations and the distribution hubs are located from these rural and distant areas. This emphasizes the significance of subsidiarity of power generation by means of renewable energy resources. Although in current energy production scenario electricity supply is principally by AC curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Remark 2: The MINLP model defined from (1) to ( 9) is a mixed-integer non-convex optimization model due to the square variables present in Equations ( 2) and ( 3) as well as the product of these in (4). However, this model can be transformed into a mixed-integer convex one using the conic representation of the power balance equations presented in [36].…”
Section: Exact Minlp Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 2: The MINLP model defined from (1) to ( 9) is a mixed-integer non-convex optimization model due to the square variables present in Equations ( 2) and ( 3) as well as the product of these in (4). However, this model can be transformed into a mixed-integer convex one using the conic representation of the power balance equations presented in [36].…”
Section: Exact Minlp Formulationmentioning
confidence: 99%
“…• The possibility of obtaining convex power flow models via conic constraints with the possibility of ensuring zero duality gap when compared with exact nonlinear nonconvex models [9]. In the specialized literature, the analyses of DC networks are made in the context of providing electric distribution applications in urban and rural areas [1,10]. The main approaches correspond to: a) optimal location and sizing of distributed generators in DC grids [11], b) optimal location and operation of battery energy storage systems [12][13][14], c) optimal reconfiguration of DC feeders [15], d) and planning of DC networks [1], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From earlier studies, it found that DC micro-grids are more feasible as PV sources, wind power generator and other renewable sources provide DC current and DC micro-grids are more stable compared to an AC micro-grid [26]. Feasibility of the energy storage system and its controls can be studied for DC grid systems proposed in [27].…”
Section: Contributions and Future Scopementioning
confidence: 99%
“…The rational of this preference is that the energy generated from solar panels is in the form of DC, energy stored in battery is DC. Further, the majority of loads are DC [6,13].…”
Section: Bipv Systems Electrificationmentioning
confidence: 99%